THE DILEMMA OF POLITICAL LEADERSHIP AND ETHNO-RELIGIOUS PLURALISM IN NIGERIA - OLANREWAJU OLU-ADEYEMI; ISIJOLA DAVID OLUSHOLA; OMOWUMI BOBOYE (Innovare Journal of Social Sciences, 2025)
Any attempt to understand the development of the nation state in Africa cannot escape a study of leadership, ethnicity, and religion as some of the main challenges to the development of democracy and nation-building. The legitimacy of the state is linked to the capacity of the political leadership to present itself as a provider of necessary public goods and, more important, a neutral arbiter that guarantees the rights, interests, and security of all sections of society. However, in Nigeria, the state, through its leadership, is generally perceived as serving the particular interest of one group, thus losing its legitimacy and indeed its authority. As state capacity declines, therefore, the fear of ‘the other’ rises and citizens resort to other levels of solidarity – ethnic and religious, in search of security. Thus, the paper utilized secondary (including historical) sources of data to show that ethno-religious pluralism and attendant conflicts have become a major theme in Nigeria’s political development over the past five decades to the detriment of nation-building. It also shows that Nigeria has witnessed a surge in ethnic chauvinism as well as Christian and Islamic religious revivalism. Rather than ethnic accommodation and secularization, there has emerged a puritanical tendency emerging in both the ethnic and religious space that has constituted a management dilemma for the political leadership. It concludes on the note that both the colonial powers and the elites that succeeded them have used ethnicity and religion for their own ends. Thus, concerted efforts to remedy the ethno-religious extremities that confront Nigeria must target poverty reduction on a massive scale among the poor on a non-ethnic basis, shift emphasis from the ‘sharing’ of the national cake to its production, promote a single form of citizenship based solely on residency requirements and re-calibrate secularism not to be the withdrawal of the state from religious affairs but as a guarantee of religious freedom to all religious groups.